2020
DOI: 10.1186/s13045-020-00889-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-driven management strategies for peripheral T cell lymphoma

Abstract: Peripheral T cell lymphomas are heterogeneous diseases which remain treatment challenges. Recent advances in molecular and genomic profiling have provided unprecedented insight into disease pathogenesis driven by distinct cells of origins and molecular pathways. The discovery and clinical application of molecular biomarkers in PTCL subtypes has the potential to transform personalized care for patients with PTCL in diagnosis, prognosis, and therapy. Targeting CD30+ PTCL with the antibody-drug conjugate brentuxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 92 publications
0
25
0
Order By: Relevance
“…Moreover, in a global double-blind, randomized phase III study, BV plus CHP (CHOP without vincristine) demonstrated higher complete remission (CR) rate and superior overall survival relative to CHOP Xie et al Exp Hematol Oncol (2020) 9:30 as frontline treatment for patients with PTCL. However, non-ALCL cases such as PTCL-NOS enrolled in this study are less than 25% [8]. Kim et al [90] reported that the disease control rate was 48.5% in the patients with R/R high CD30-expressing NHL including PTCL-NOS (24.2%), ENKTL (21.2%) and AITL (3%).…”
Section: Targeting Cell Surface Moleculesmentioning
confidence: 70%
See 3 more Smart Citations
“…Moreover, in a global double-blind, randomized phase III study, BV plus CHP (CHOP without vincristine) demonstrated higher complete remission (CR) rate and superior overall survival relative to CHOP Xie et al Exp Hematol Oncol (2020) 9:30 as frontline treatment for patients with PTCL. However, non-ALCL cases such as PTCL-NOS enrolled in this study are less than 25% [8]. Kim et al [90] reported that the disease control rate was 48.5% in the patients with R/R high CD30-expressing NHL including PTCL-NOS (24.2%), ENKTL (21.2%) and AITL (3%).…”
Section: Targeting Cell Surface Moleculesmentioning
confidence: 70%
“…Using GEP, two biological subgroups of PTCL-NOS have been identified, which include PTCL-GATA3 that is characterized by high expression of GATA3 and known target genes (CCR4, IL18RA, CXCR7, and IK), and PTCL-TBX21 that shows significantly higher expression of TBX21 (T-bet) and EOMES and their downstream targets (CXCR3, IL2RB, CCL3, IFN-γ) [6,7]. The transcription factors TBX21 and GATA3 promote differentiation of CD4 + T cells into TH1 and TH2 helper cells, respectively [8]. The PTCL-GATA3 subgroup, accounting for 33% of PTCL-NOS, has an enrichment of MYC and cytotoxic gene with poorer outcome while the PTCL-TBX21 subgroup that constitutes 49% of PTCL-NOS, has a tumor microenvironment gene signature and is associated with a favorable outcome.…”
Section: Peripheral T-cell Lymphoma Not Other Specified Typementioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity to molecular targeted therapy usually varies among individual cancer patients and at different stages of tumor progression. Elucidation of the mechanisms underpinning the sensitivity to molecular targeted agents may help identify the appropriate biomarkers to stratify patients for precision cancer therapy [ 236 , 237 ]. Akt-dependent tumors may be vulnerable to therapeutic Akt inhibition.…”
Section: Biomarkers and Molecular Basis Of Response To Akt Inhibitors In Cancermentioning
confidence: 99%